Factors Influencing Construction Technology Teachers' Ability to Conduct Simulations Effectively (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The efficacy of teaching hands-on skills practical activities requires teachers' willingness to implement technology enhanced pedagogy through the creation of relevant subject simulations. Teachers should be competent with workplace basics in order to prepare and demonstrate construction practical lessons that promote undeniably marketable skills that students can use to contribute to this competitive economy. The goal of this research was to look into the factors that influence Construction Technology teachers' effective teaching when conducting simulations. Purposive sampling was used to identify a total of five (5) teachers to participate in this study. Non-participant observation and semi-structured interviews were also used as a complementary data collection tool. The conceptual framework that guided this study workplace basics. According to the findings of this study, most Construction Technology teachers lack basic workplace skills as well as the ability to maintain effective teaching when conducting simulations. This is due to poorly made artifacts and a failure to use all available tools and equipment. Furthermore, the study discovered that teachers do not always plan for their theory lessons, and the challenge is even more difficult for practical lessons. The study suggests that Construction Technology teachers attend practical skill development training for Curriculum Assessment Policy Statement (CAPS) 2 while also visiting industries, universities, and colleges to gain exposure to the trade environment in order to stay current with technological developments. Most importantly, teachers should engage in ongoing professional development and learn the fundamentals of the workplace basics skills.